A Feasibility study on tornado clothes dryer - Calayag, Lauran N.; Montefalcon, Anna Ricelle D.; Mosqueda, Ma. Melissa E.; Redillas, Joshua E. (College of Engineering, 1999)
The TornadoTM clothes dryer is made up of many parts, many of which are made of plastic and others made of metal or steel. The base, clothes rack, dome, drainage, drain pan, fan guard, and housing are made of ABS plastic. ABS plastic stands for acrylonytrile-butadiene-styrene, which is a thermoplastic. The product 100% dries up clothes. It eliminates the probability of material damage, easily assembled, movable and a space-saver. A market study on the product identified the target market to be primarily households having an income, which belongs to bracket A, B, and C. With the demand exceeding supply, the group established a market share of 21.78% for the next five years. However, due to production constraints, market share for year 2003 and 2004 was decrease to 21.4% and 21.0% respectively. The product costs Php 5,500, and an aggressive marketing in the form of print media, brochures, product launch, web sites, product demonstrations, make it feasible for the product to penetrate the industry. The total marketing budget for the introduction of the product is Php 3.8 million. The technical analysis of the production of the product showed that the company will mold the plastic parts of the product and buy the fan blade and other pre-fabricated metal parts from different suppliers. The mode of production will be, mainly, assembly. This kind of production will require 2 moulding machines, 3 storage areas and 1,437 sq. m of land. A total of 29 administrative and support staff and 28 production workers are needed on the first year and four years thereafter. Three shifts of workers will be needed to man the 1600 ton machine. The plant having an area of 1,600 sq. m located in Pasig City can accommodate all these requirements. The total project cost for the first year of operation is Php 318,358,358.60. In the organization and management study, the form of organization established to pursue the project is that of a corporation. It shall be composed of the plant manager, six department heads and support staff. A total of 29 administrative and support staff and 28 workers will be employed by the corporation. The results of the financial analysis showed that the product is financially feasible and attractive. The project is both profitable as shown by the financial ratios which also revealed the company is both liquid and solvent for the first five years of operation. The net present value of the project amounts to Php 194,905,907.44 with an internal rate of return equal to 98% compared to a minimum attractive rate of return of 25% and a payback period of 2 years. A listing of the costs and benefits in undertaking the project was provided in the social profitability analysis. Far-reaching benefits to both the community in the chosen site and the local and national government were identified. These include the additional employment opportunities, payment of municipal, corporate and individual income taxes of the corporation. It can, therefore, be concluded that TornadoTM clothes dryer has a sufficient market, is technically feasible, is financially feasible and is socially profitable to all entities affected.